A novel quartile deviation score evaluation (QDSE) method to minimize uncertainty in evaluation of solid waste management. (2022) - Kumar, Raman; Singh, Harwinder; Singh Chohan, Jasgurpreet
Abstract: In this globalized era, individuals and organizations are concentrating on better decision making, which helps in the successful waste management, materials management and operation of the business. This research work presents a novel decision-making method and its applications using a quartile concept. The complexity in methodology may affect the credibility of the final results; consequently, a simple and logical QDSE method is presented to evaluate the best alternative in the decision-making problem. To validate the effectiveness of QDSE, a published example in which QDSE method results are not alike to TOPSIS and PROMETHEE method is demonstrated and it has been logically proved that QDSE results are more reliable. The application of QDSE method is presented in selection of solid waste management by demonstrating examples. Moreover, the proposed method can be applied in any multi-criteria decision-making process.